Role of repeat procalcitonin estimation at 48 hours for outcome in pregnancy associated sepsis: a prospective observational study - Rachna Agarwal; Kavita Sharma; Mohit Mehndiratta; Medha Mohta; Himsweta Srivastava; Almeida Edelbert Anthonio (Korean Society of Obstetrics and Gynecology, 2021)
Objectives We assessed whether repeat procalcitonin (PCT) estimation has a role in detecting organ dysfunctions and mortality in pregnancy associated sepsis (PAS). Methods The study included 85 pregnant, post-abortal, and postpartum women with PAS, diagnosed using the quick Sequential Organ Failure Assessment criteria. Median interquartile range PCT levels were documented at admission and 48 hours later. Statistical comparisons were performed between the groups with non-severe and severe (≥1 organ failure) PAS, and between the survivor and mortality groups. The relationship between PCT and the number of organ failures was also assessed. Results Most of the subjects with PAS were young and in the postpartum period (mean age 26 years; postpartum 55%). Sixteen (19%) patients died due to PAS. Sixty-two patients (74%) had severe PAS at presentation. Bacteria were isolated on culture in 64% of the subjects. PCT levels at admission were higher in patients with severe PAS than in those who did not have severe PAS. At 48 hours, this difference was significant (P=0.014; severe PAS 2.23 ng/mL vs. non-severe PAS 0.20 ng/mL). Furthermore, the number of organ failures increased at 48 hours. The PCT levels were significantly higher in the mortality group than in the survivors' group at admission (8.31 ng/mL vs. 1.72 ng/mL), and the difference increased further at 48 hours (9.54 ng/mL vs. 1.37 ng/mL). Conclusion Repeat PCT estimation at 48 hours could complement the clinical findings and enhance the prognostic value for PAS.